Implementation of Transparency and Accountability in Financial Management of Village Fund Allocations 2022 in Pandai Village, Woha District Bima Regency - Ari Anggareka (Yayasan Amerta Insan Unggul, 2024)
This study examines the implementation of transparency and accountability in the financial management of Village Fund Allocations (ADD) in Pandai Village, Woha District, Bima Regency. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation involving key informants such as the village head, secretary, treasurer, and community representatives. The research aims to identify how transparency and accountability principles are applied across planning, implementation, and reporting stages. The findings indicate that the village government of Pandai has implemented these principles effectively by ensuring community involvement in decision-making processes and providing public access to financial information through notice boards and periodic reports. Transparency is reflected in participatory planning and open disclosure of fund utilization, while accountability is demonstrated through timely financial reporting and adherence to regulatory frameworks. The consistent application of these principles has strengthened good governance practices, improved public trust, and enhanced community participation in local development initiatives. However, continuous monitoring, evaluation, and capacity building for village officials are necessary to ensure sustainability and mitigate potential risks of mismanagement. Overall, this study underscores that transparency and accountability serve as essential pillars for effective village fund management, promoting equitable development and reinforcing the integrity of public financial governance in rural Indonesia.